Studi Kualitatif Layanan Kesehatan Yang Diterima Orang Dengan HIV: A Qualitative Study of Health Services Received by People Living with HIV - Gusti Sumarsih; Mahathir; Devia Putri Lenggogeni (Fakultas Keperawatan Universitas Andalas, 2023)
Comprehensive health care service is right for people living with HIV/AIDS. It is important to know and dig deeply into the needs of healthcare services among people living with HIV as a vulnerable group. Exploration of healthcare provider services received by people living with HIV can provide a thick description related to the process of care and treatment. In-depth interviews were conducted with nine people living with HIV who utilize healthcare services in Jakarta. In this phenomenological qualitative study, researchers have used the data analysis stage according to Stevick-Colaizzi. This study identifies the essence of the healthcare received by people living with HIV as healthcare services information, easy access to healthcare services, services before the test, services after the test, getting ARVs, and treatment of health complaints. The findings recommend that healthcare providers further optimize their services to give a real impact in the prevention of the HIV/AIDS pandemic.